2013
DOI: 10.1111/ijfs.12122
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antifungal activities of selected microalgae and cyanobacteria

Abstract: In vitro activity of nine cyanobacterial and ten microalgal newly isolated or culture collection strains against eight significant food-borne pathogens has been evaluated and compared. Water extracts and culture liquids of Gloeocapsa sp. and Synechocystis sp. demonstrated the widest spectrum of activity with minimal inhibitory concentration (MIC) ranging from 1.56 to 12.5 mg mL À1 . Culture liquid of Anabaena sp. had the highest activity (MIC = 0.39 mg mL À1 ) but only to Gram-positive bacteria. Ethanol extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 35 publications
(33 reference statements)
1
97
0
4
Order By: Relevance
“…This showed that the methanol extracts have significant antifungal activity. Najdenski et al (2013) The presence of antimicrobial activity is affected by both algal species and the solvents use for their extraction (Radhika, Veerabahu, & Priya, 2012). The antimicrobial activity of algae extracts is generally assayed using various organic solvents which always provide a higher efficiency in extracting compounds for antimicrobial activity (Tüney, Çadirci, Unal, & Sukatar, 2006).…”
Section: Candida Albicansmentioning
confidence: 99%
“…This showed that the methanol extracts have significant antifungal activity. Najdenski et al (2013) The presence of antimicrobial activity is affected by both algal species and the solvents use for their extraction (Radhika, Veerabahu, & Priya, 2012). The antimicrobial activity of algae extracts is generally assayed using various organic solvents which always provide a higher efficiency in extracting compounds for antimicrobial activity (Tüney, Çadirci, Unal, & Sukatar, 2006).…”
Section: Candida Albicansmentioning
confidence: 99%
“…The associated increase in fungal infections prompted search for newer and safer agents to combat fungal infections [32] and a few noteworthy results encompassing microalgae are listed in Table 3 [19,24,33].…”
Section: Antiviral Activity Of Algaementioning
confidence: 99%
“…The development in the field of algal therapeutic research has made it possible by their bioactive compounds which have been found effective against most of the pathogens (Figures 1 and 2). The list of some of the algal bioactive compounds is summarized in the Table 1 [ [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Its fatty acids also had a potential activity against these cells. [1,3,4] These interesting results raised the question about the strain identification, additional to the general knowledge that it belongs to the unicellular green autosporic genus Chlorella Beijerinck. The simple morphology of this genus causes taxonomical difficulties, discussed by many authors for a very long time.…”
Section: Introductionmentioning
confidence: 99%